2022
DOI: 10.3389/fncel.2022.915587
|View full text |Cite
|
Sign up to set email alerts
|

Will Sirtuin 2 Be a Promising Target for Neuroinflammatory Disorders?

Abstract: Neuroinflammatory disorder is a general term that is associated with the progressive loss of neuronal structure or function. At present, the widely studied diseases with neuroinflammatory components are mainly divided into neurodegenerative and neuropsychiatric diseases, namely, Alzheimer’s disease, Parkinson’s disease, depression, stroke, and so on. An appropriate neuroinflammatory response can promote brain homeostasis, while excessive neuroinflammation can inhibit neuronal regeneration and damage the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…AXIN1, for example, a regulator molecule of the Wnt signaling pathways [ 75 ], has been shown to correlate with disease severity in endometriosis [ 76 ]. SIRT2 has a wide range of regulatory functions ranging from neuronal to immunological and metabolic homeostasis [ 77 , 78 ]. Our study, together with other protein disease signature (PDS) studies, shows the importance of analyzing multiple inflammatory markers and comorbidities to explore a more complete picture of a disease.…”
Section: Discussionmentioning
confidence: 99%
“…AXIN1, for example, a regulator molecule of the Wnt signaling pathways [ 75 ], has been shown to correlate with disease severity in endometriosis [ 76 ]. SIRT2 has a wide range of regulatory functions ranging from neuronal to immunological and metabolic homeostasis [ 77 , 78 ]. Our study, together with other protein disease signature (PDS) studies, shows the importance of analyzing multiple inflammatory markers and comorbidities to explore a more complete picture of a disease.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The transcellular delivery of this protein from oligodendrocytes to neurons via exosomes plays a vital role in CNS function. 16 SIRT2 is implicated in neuropsychiatric disorders, 23 and clinical studies have indicated that SIRT2 transcript is reduced in peripheral leukocytes and hippocampal tissues of depressed patients. 24 , 25 In rodents, reduced hippocampal SIRT2 is associated with the progression of depression and impaired neuroplasticity, while SIRT2 overexpression can enhance hippocampal neurogenesis and alleviate depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT-2 has been extensively examined for its involvement in influencing senescence, myelin formation, autophagy, and inflammation. These has been linked with numerous neuroinflammatory pathologies as it contains deacetylation characteristics that affect immune homeostasis ( 27 ). SIRT-3, SIRT-4, and SIRT-5 are mitochondrial proteins that are strongly connected to mitochondrial function and play a key role in the development of COPD-associated mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%